Study of the book Hashiyat Al-Imam Ibn Bilal Al-Hanafi (d. 957 AH) on the explanation of Mukhtasar Al-Muntaha for Al-Udud - ALthobaiti, Reem Ahmed (Journal of Islamic Sciences, 2023)
The aim of this research was to familiarize the Hashiyat of Imam Ibn Bilal through familiarizing the title of the book Hashiyat al-Imam Ibn Bilal al-Hanafi, its attribution to the author, its written copies, its content, sources, and the author's approach to it.This research relied on descriptive analytical method and inductive method.This research concluded that Ibn Bilal made his Hashiyat depending on Ibn Al-Hajeb's Mukhtasar Al-Muntaha, his explanation of Al-Adhd, and Taftazani's Hashiyat. Also, It found that Ibn Bilal confined his Hashiyat to fundamentalist principles, which consist of (83) comments, most of which are logical comments, grammatical, rhetorical and fundamentalist.
Keywords: Ibn Bilal's; Hashiyat the Mukhtasar; Hashiyat the explanation AL-Udud